Harvesting spontaneous vegetation or purchase medicinal plants from the market? – case study - Manole, Victor; Istudor, Nicolae; Popescu Cristian, George (Economics of Agriculture, 2010)
The paper analyses the effciency of material resources supplying of an enterprise that processes medicinal herbs. The objectives of the research are to identify the most cost-effective alternative of supplying herbs, out of two possible sources: spontaneous vegetation, by initiating a campaign of collection, or purchase them from contractors. Econometric models are developed for choosing the optimal solution, entering data from a business of processing medicinal herbs in a computer program. The results show that there is a quantity of material resources for which is more proftable to get it by initiating a campaign of collecting plants from spontaneous flora, after which, for any additional quantity, it becomes more effcient to be purchased from the market.